A study on limnological aspects of Ramsagar lake in Dinajpur district (Journal of the Bangladesh Agricultural University, 2016)
Limnological aspects of the Ramsagar lake, a manmade lake of Dinajpur district was studied from January 2013 to August 2013. In this experiment, five sampling points inside the Ramsagar lake were selected and water quality parameters were analyzed fortnightly. Among different physico-chemical parameters, water temperature, dissolved oxygen, total alkalinity, total hardness, phosphate-phosphorus and concentration of Chlorophyll-a did not differ significantly except the water level and pH. A total of 29 species of plankton were recorded where phytoplankton comprised of 21 species and zooplankton comprised of 8 species. Chlorophyceae was found dominant throughout the study period followed by Bacillariophyceae, Cyanophyceae and Euglenophyceae. The highest plankton cell density was observed in the month of July and lowest plankton density was observed during the month of January. The study revealed that on the basis of physical, chemical, biological and environmental conditions the water of the lake was found to be suitable for survival of aquatic flora and fauna and also suitable for fish culture.J. Bangladesh Agril. Univ. 13(1): 145-152, June 2015